Serial Rectifier Antenna (Rectenna) Microstrip Patch Circular 2.4 Ghz For Radio Frequency Energy Harvester - Nadya Friska Friska; Nasrul Nasrul; Rikki Vitria (International Journal of Wireless And Multimedia Communications, 2024)
The source of Radio Frequency  (RF) electromagnetic wave energy in the atmosphere is currently abundant and wasted due to the rapid development of RF technology today. Utilizing the rectenna system to harvest energy, this RF energy source can be used as an environmentally friendly distribution method. To improve the rectenna's ability to convert electromagnetic waves into direct voltage (DC) sources, a rectenna antenna  system was designed using a serial rectenna system. using 3 antennas and 3 rectifier circuits, to design a  serial rectenna system. A circular patch microstrip antenna with a frequency of 2.4 GHz is used in serial receiving systems to receive WiFi signals.  Schottky 2860 diodes and 1nF smd capacitors are used in the 6-stage voltage multiplier of the rectifier circuit,  which is used in the rectifier.  Round patch microstrip antennas were found to be capable of capturing and directing voltage to DC through testing and measurement of rectenna serial systems. The system antenna has return loss values of -26.29 dB, -21.75 dB, and -28.57  dB,  VSWR 1.11,  1.16, and 1.07,  impedance 51.1,  55.56, and    50.22, and bandwidth of 60 MHz .  The resonant frequencies for 60 MHz and 50 MHz are 2.42 GHz, 2.36 GHz, and 2.48 GHz. so that at a distance of 25 cm a single rectenna system produces a voltage of 51 points 3 mV. During this time, the serial receiver system can change a direct voltage of  151.08 mV at a distance of 25 cm from the Access Point transmitter source.